Perfil clínico-epidemiológico de coinfecciones en pacientes con pénfigo foliáceo endémico en el Hospital Regional de Loreto 2014-2024 - Canayo López, Johnny Léster (2025)
Endemic pemphigus foliaceus (EPF) represents a high-prevalence autoimmune disease in the Amazon region, particularly in Loreto, where coinfections significantly contribute to morbidity and mortality. This study aims to clinically and epidemiologically characterize coinfections in adult patients with confirmed EPF diagnosis treated at the Hospital Regional de Loreto between 2014 and 2024, identifying their frequency, risk factors, diagnostic methods used, and clinical outcomes, specifically therapeutic response, hospitalization, and associated mortality. A retrospective, cross-sectional, analytical study will be performed by reviewing medical records, microbiological data, and treatments given. Data analysis will employ descriptive statistics, bivariate tests, and multivariate logistic regression models at a 95% confidence level. A high frequency of bacterial, fungal, and viral coinfections is expected, associated with factors such as prolonged immunosuppression, delayed diagnosis, and deficiencies in access to safe water. Diagnostic gaps are also anticipated, including limited access to specific culture and sensitivity testing, and therapeutic gaps such as frequent empirical use of broad-spectrum antimicrobials, factors limiting comprehensive management of these patients. The results will generate unprecedented local evidence to design clinical protocols adapted to the Amazonian context, focused on rational antimicrobial use, timely diagnosis, and community prevention. This research seeks to strengthen public health strategies in highly vulnerable regions.